O turismo e suas implicações em municípios de pequeno porte demográfico da região turística noroeste do Paraná - Alves, Larissa de Mattos (2018)
This study aims to analyze the implications of tourism in small demographic municipalities of the Northwest Paraná region. These municipalities suffer from population losses, a poorly inclusive economy, few jobs and rare leisure and entertainment options. The analyzes which reflect on tourism capacity to contribute to scenario?s reversal economic stagnation and local development are organized into five chapters. In the first one, we reflected on the adequacy of public tourism policies in Brazil to small demographic municipalities, considering their goals and what geographical scales and demographic sizes were contemplated. In the second one, we analyzed the 65 tourism development inductive destinations in Brazil, establishing a relationship between the different demographic dimensions, their attractions, products and tourism services offered. In the third chapter, the analyzes were delimited to the tourist region Northwest of Paraná, starting from the state presentation context and the municipalities demographic sized. Among 98 small demographic region towns some of them stand out turistically and were selected for their particularities such as: Iguaraçu, Iretama, Puerto Rico and Terra Boa. In 2014, Iguaraçu, Iretama and Puerto Rico had the largest job number while Mtur resources transferred to small demographic municipalities showed the reach of Terra Boa among the others. The fourth chapter is devoted to analyzing the implications of the different tourist modalities in these four municipalities, evaluating the scope and limits of tourism in Paraná Northwest region. The last but not least chapter of this work, we have elaborated a comparative study about the implications of tourism in small demographic municipalities. We consider Iguaraçu, Iretama, Puerto Rico and Terra Boa, their micro and mesoregions in the foreground, but other Brazilian and Portuguese tourist realities such as Coruche, Montemor-o-Novo and Óbidos were considered to complement the comparative analyzes. The present research required, mainly, bibliographic review, document analysis and field studies that involved the permanence and local products consumption, observation, interviews and consultations with residents and tourists during the use of public spaces, equipment and tourist services. We observed that there is no public policy to support or stimulate tourism development in small municipalities. These have very specific demands and therefore require special attention to enter the competitive market of tourist destinations. Analyzes and comparisons between tourist municipalities of different demographic sizes indicated that both private investments from international hotel chains and public ones are concentrated in large cities, with small towns remaining on the margins of this process. It is possible to point out, as the main economic achievements of the sector, jobs and the economic dynamization resulting in Iguaraçu and Iretama. Among the socio-environmental achievements, we highlight Puerto Rico natural resources conservation and its cultural manifestations and the expansion of leisure options in the four municipalities. The analyzes made it possible to perceive that there is a significant contribution of tourism, but it is not appropriate to place in this activity all the responsibility for the economic dynamization necessary to support the local development, because in this case the segment will hardly correspond